Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Gladstone on Candide, edited by Theodore Besterman J. D. Hubert, Note malicieuse sur le jardin de Candide Robert S. Tate, Manon Lescaut and the Enlightenment Frederick Plotkin, Mime as pander: Diderot's Neveu de Rameau Madeleine Molinier, Les Relations de Deleyre et de Rousseau, 1753-1778, suivi de la correspondance inédite de Deleyre et du marquis de Giradin, août-décembre 1778 Marie José Southworth, La Notion de l'île chez Rousseau Rémy G. Saisselin, The Transformation of art into culture: from Pascal to Diderot Darlene Gay Levy, Simon Linguet's sociological system: an exhortation to patience and invitation to revolution